A lotus effect-inspired flexible and breathable membrane with hierarchical electrospinning micro/nanofibers and ZnO nanowires. (15th January 2019) - Chen, Rouxi; Wan, Yuqin; Wu, Weiwei; Yang, Cao; He, Ji-Huan; Cheng, Jianhua; Jetter, Reinhard; Ko, Fank K.; Chen, Yuancai
Abstract: Hierarchical structures such as the leaf of lotus are promising models for self-cleaning surfaces. A biomimetic structure that contains PVDF microfibers (ZnO nanowires covered with oleic acid) was prepared here to illustrate the biomimetic lotus effect concept. This was prepared via electrospinning, hydrothermal synthesis, and dip coating. The hierarchical structure and oleic acid coating was shown to contribute to super hydrophobicity with a water contact angle (WCA) > 150°. The super hydrophobic flexible membrane not only exhibited water droplet bouncing and rolling behaviors, but also demonstrated promising self-cleaning properties, water resistance, and permeability of air and water vapor. These characteristics have far reaching implications in broadening the application of the self-cleaning textiles, waterproof breathable membrane, medical devices, and surgical plants such as artificial blood vessels. Graphical abstract: